Combined hot corrosion and static stress or fatigue of single crystal superalloys. - Brooking, Laurie Finian (Cranfield University, 2018)
It has been observed that gas turbine (GT) blades operating in harsh environments can undergo material degradation in the form of crack initiation and propagation before that predicted by fatigue lifing. It is thought that this degradation can occur partly as a result of the growing demands for improved GT efficiencies. This is because the requirement for improved GT efficiencies is commonly achieved through increases in operational temperatures and pressures which the turbine stages operate at. These increases in the operational temperatures can consequently lead to the extended effect of hot corrosion in locations of the blade which would not normally impacted, such as the under platform region. Therefore, GT blades are subjected to continuous developments in terms of blade design and material properties and selection in order to achieve improvement in the GT efficiencies, reduce emissions and lower life cycle costs. However, at start of this research project it was postulated that the mechanism causing premature material degradation is a result of the extended effects of low temperature hot corrosion (LTHC), interacting with both cyclic and static loading conditions. In order to experimentally study these interactions statically and cyclically loaded specimens were tested in environments representative of the under platform region of both industrial and aviation gas turbine (GT) blades. A range of geometries were studied: C-rings, three point bend and cylindrical fatigue specimens. Using these specimens experimental studies were conducted investigating the impact of deposit flux, dwell time, multiaxial stress state and load application rate. Further investigations into the microscopic mechanism occurring at the crack tip have been conducted using high magnification transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Detailed stress state data has been produced using finite element analysis (FEA), this data has then been used to assess the impact of the stress state on crack initiation and propagation. It was found that turbine blade materials were susceptible to a form of high temperature stress corrosion cracking (SCC). Additionally, enhanced fatigue crack initiation and propagation was observed with test conditions consistent with low temperature hot corrosion (LTHC) conditions. There was shown to be a detrimental impact with increased rates of LTHC on the high temperature cracking mechanism. Detailed microscopy and analysis of specimens informed a proposed fundamental mechanism behind the enhanced cracking observed in LTHC environments. The five research papers presented within this thesis provide contributions to knowledge and developments in the understanding of crack initiation and propagation within superalloys exposed to simultaneous LTHC environments and loading.
Keywords: Single crystal superalloys; hot corrosion; fatigue; corrosion cracking; FEA